متطلبات تطبيق الإدارة الإلكترونية في كلية الاقتصاد والمحاسبة بجامعة سبها من وجهة نظر الإداريين وأعضاء هيئة التدريس العاملين بها (Journal of Academic Research, 2019)
The aim of this study is to identify the availability of the requirements of the application of electronic administration in the Faculty of Economics and Accounting at the University of Sabha, from the point of view of administrators and Lecturers of the Faculty, as well as presenting some suggestions for the development of the requirements of electronic administration in the Faculty of Economics and Accounting at the University of Sabha, from the point of view of administrators and Lecturers of the Faculty, This study was applied to a random sample of 45 Lecturers and administrators of faculty, the researcher used descriptive analytical approach to achieve the goal of the study, the researcher prepared a questionnaire includes several areas of the requirements of the application of electronic administration,(Administrative requirements Physical requirements Technical requirements Human requirements Financial requirements Safety and security requirements), the SPSS statistical program was used to analysis data, the study concluded that there is a low level of the application of the electronic administration in the Faculty for all the requirements under study.